Negotiating a Pedagogy. The Essential Elements and Fundamental Principles of the Fiddle Pedagogy of Pádraig O' Keeffe - Barrett, Noelle (Trinity College (Dublin, Ireland). School of Education, 2021)
Pádraig O’Keeffe (1887- 1963), a highly regarded fiddle teacher was one of the greatest musicians from the Sliabh Luachra region in Co. Kerry, indeed from the entire country. O’Keeffe’s seminal style of playing which is referred to as the Sliabh Luachra style is revered world-wide. While much is written on the unique performance style of this great musician there is very little scholarship into his teaching style. This study was conducted to investigate the teaching style of fiddler and renowned teacher Pádraig O’Keeffe. Based on a series of seven in-depth interviews with exponents of O’Keeffe’s tradition, this exploratory qualitative study aimed to elicit a body of information regarding the unique pedagogic style of this renowned performer and teacher. Specifically, the study investigated how the seven participants, now all practicing musicians, made meaning of that specific pedagogical style. Fieldwork was conducted over three months using in-depth semi-structured interviews. These individual interviews allowed access to participants’ representations of their experiences of either being taught by O’Keefe directly (2 participants), being taught by someone who was themselves taught by O’Keeffe (4 participants) or who learned from recordings of O’Keeffe’s music (1). Analysis at stage one involved a coding and categorization process based on Keegan’s (2010) performance indicators. In stage two, codes and categories were compared with significant themes from the extant literature. Building upon insights generated at stage one and two, stage three aimed at describing the essential elements of this inimitable teaching style. Four main findings relating to O’Keeffe’s pedagogical style emerged. These include, Modelling, Enculturation, Learning resources and Interpretation. These findings expand on the scant academic literature which deals with O’Keeffe’s contribution to teaching.
Keywords: Music in Education; Education